Drying kinetics of white mulberry - Doymaz, I (ELSEVIER SCI LTD, 2004)
In this study, thin layer air-drying experiments of mulberries grown in Istanbul, Turkey, were conducted. The effect of pretreatment solutions such as ethyl oleate, citric and ascorbic acid solutions on drying time of mulberry samples was investigated in a pilot air-dryer. For mulberries dried with heat shock and ethyl oleate, drying time decreased over that of other pretreatments and untreated fruit. Six different thin layer mathematical drying models were compared according to their coefficient of determination to estimate drying curves. The effective moisture diffusivity values were estimated from Fick's diffusion model. These values were in the range 2.231-6.909 x 10(-10) m(2)/s. Comparing the r(2), SSE and RMSE values of the six models, it was concluded that the logarithmic model represents drying characteristics better than the other equations. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: mulberry; drying; pretreatment solution; mathematical models; DIPPING TREATMENT; SEEDLESS GRAPES; SULTANA GRAPES; PRETREATMENTS; DEHYDRATION; APRICOTS; RAISINS; SLICES; SUN; Engineering; Food Science & Technology